The Impact of Valuation Requirements on the Preferred Stock Investment Policies of Life Insurance Companies (Book). - Zeff, Stephen A.; Goshay, Robert C. (The Accounting Review, 1965)
Reviews the book "The Impact of Valuation Requirements on the Preferred Stock Investment Policies of Life Insurance Companies," by Alden C. Olson.